Probing into the boredom of online instruction among Chinese English language teachers during the Covid-19 pandemic - Wang, Yongliang (Current psychology (New Brunswick, N.J.), 2024)
Although researching emotions in language education has dramatically increased during the past decades, little is written about the effects of aversive feelings like teacher boredom in the English as a foreign language (EFL) context, especially in the context of online instruction during the COVID-19 pandemic. Against this shortcoming, this study examined the causes of and solutions to teacher boredom experienced by 216 Chinese EFL teachers, including both genders with their ages ranging from 19 to 58. In so doing, the researcher used maximum variation sampling to gather the data via an open-ended questionnaire and semi-structured interviews. The gleaned data were then thematically analyzed by MAXQDA (Version 2020) whose results indicated that most participants consider the online mode of delivery more boring than the face-to-face mode. Additionally, the findings demonstrated that both the antecedents of and the solutions to teacher boredom come under the macro-categories of student-related, task-related, IT-related , and teacher-related factors and solutions. Out of these, IT - related factors and teacher-related solutions were the most frequently raised themes extracted from the data. The study presents some practical implications and directions for future research.